Factors affecting visualization of postmenopausal ovaries: descriptive study from the multicenter United Kingdom Collaborative Trial of Ovarian Cancer Screening (UKCTOCS). (23rd September 2013) - Sharma, A.; Burnell, M.; Gentry‐Maharaj, A.; Campbell, S.; Amso, N. N.; Seif, M. W.; Fletcher, G.; Brunel, C.; Turner, G.; Rangar, R.; Ryan, A.; Jacobs, I.; et al.
ABSTRACT Objective Transvaginal sonography (TVS) is core to any ovarian cancer screening strategy. General‐population screening involves older postmenopausal women in whom ovarian visualization is difficult because of decreasing ovarian size and lack of follicular activity. We report on factors affecting the visualization of postmenopausal ovaries in the multicenter United Kingdom Collaborative Trial of Ovarian Cancer Screening (UKCTOCS). Methods The UKCTOCS is a randomized controlled trial of 202 638 postmenopausal women with 50 639 women in the ultrasound scan arm. TVS is the primary screening modality in the ultrasound scan arm. Age, education, ethnicity, body mass index (BMI), previous pelvic surgery, lifestyle and reproductive factors, and a personal/family history of cancer were assessed for their effects on ovarian visualization at the initial TVS. Results Between 11 June 2001 and 18 August 2007, 43 867 women underwent TVS. The median age and BMI of the women were 60.6 (interquartile range (IQR), 9.9) years and 25.7 (IQR, 5.8), respectively. The right ovary was visualized in 29 297 (66.8%) and the left ovary was visualized in 28 726 (65.5%). Visualization of ovaries decreased with previous hysterectomy (odds ratio (OR) = 0.534; 95% CI, 0.504–0.567), previous tubal ligation (OR = 0.895; 95% CI, 0.852–0.940), increasing age (OR = 0.953; 95% CI, 0.950–0.956), unilateral oophorectomy (OR = 0.224; 95% CI, 0.186–0.269) and being overweight (OR = 0.918; 95% CI, 0.876–0.962) or obese (OR = 0.715; 95% CI, 0.677–0.755). Increased visualization was observed with a history of infertility (OR = 1.134; 95% CI, 1.005–1.279) and increasing age (in years) at menopause (OR = 1.005; 95% CI, 1.001–1.009). Conclusions Several factors affect the visualization of postmenopausal ovaries. Their impact needs to be taken into consideration when developing quality assurance for ovarian ultrasound scanning or comparing study results as their prevalence may differ between populations. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.